2022
DOI: 10.1016/j.jmbbm.2021.105042
|View full text |Cite
|
Sign up to set email alerts
|

Bending properties of additively manufactured commercially pure titanium (CPTi) limited contact dynamic compression plate (LC-DCP) constructs: Effect of surface treatment

Abstract: BackgroundAdditive manufacturing of metallic materials, a layer-wise manufacturing method, is currently gaining attention in the biomedical industry because of its capability to fabricate complex geometries including customized parts tting to patient requirements. However, one of the major challenges hindering the full implementation of additively manufactured parts in safety-critical applications is their poor mechanical performance under cyclic loading. This study investigated both quasi-static bending prope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Thus, it is necessary to remove surface defects and/or reduce surface roughness using other methods such as machining [25]. It has been reported that the fatigue life of PBF/ Ti6Al4V decreases with an increase in the maximum surface roughness [26], and the surface roughness affects the fatigue strength of PBF/ Ti6Al4V [27][28][29][30][31], thus a reduction in the surface roughness of PBF/ Ti6Al4V is required to improve the fatigue properties. To reduce surface roughness of PBF metals, mechanical surface finishing [32], ultrasonic cavitation abrasive finishing [33], chemical etching [34], ultrasonic shot peening [35], cavitation abrasive surface finishing [36,37], hydrodynamic cavitation abrasive finishing [38,39], barreling [40], and linishing [40] have been proposed, and the improvement of fatigue strength of PBF/Ti6Al4V was demonstrated [32,36,37,40].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to remove surface defects and/or reduce surface roughness using other methods such as machining [25]. It has been reported that the fatigue life of PBF/ Ti6Al4V decreases with an increase in the maximum surface roughness [26], and the surface roughness affects the fatigue strength of PBF/ Ti6Al4V [27][28][29][30][31], thus a reduction in the surface roughness of PBF/ Ti6Al4V is required to improve the fatigue properties. To reduce surface roughness of PBF metals, mechanical surface finishing [32], ultrasonic cavitation abrasive finishing [33], chemical etching [34], ultrasonic shot peening [35], cavitation abrasive surface finishing [36,37], hydrodynamic cavitation abrasive finishing [38,39], barreling [40], and linishing [40] have been proposed, and the improvement of fatigue strength of PBF/Ti6Al4V was demonstrated [32,36,37,40].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical stabilization using metal implants or plates is regular in medical practice, especially for fracture fixation, and such implants are convenient to personalize utilizing AM. 13,47 Such implants could be custom modified not just based on the nature of the injury but also could facilitate alterations in surface roughness, topography, and drug loading. 15,48 The customized implants also provide flexibility with site specificity of multifunctional coatings, 17 improve osseointegration, 3 and antibacterial deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Laser powder bed fusion (L-PBF) techniques can be used to manufacture metal implants, by using a high-powered laser to scan a powder material bed and fuse particles forming the desired geometry through layer upon layer fabrication . In addition, various modifications are also being attempted on these accepted techniques involving fine gas-atomized powders and laser polishing to improve microstructure, elongation, corrosion resistance, surface finishing, and biocompatibility of the implants. ,, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations